Once again on the authorship of La Celestina (Letras, 2019)
The problem of Celestina’s authorship —whether there was one (Fernando de Rojas) or more authors— has been controversial along the Spanish history of literature. In this article I question if Fernando de Rojas, bachelor of Puebla de Montalbán who belonged to a family of converts, and became Mayor of Talavera, was really Celestina’s creator. To support this idea I review many different opinions about Celestina’s authorship until today, when doubts far exceed the certainties. Many critics (including myself) do not accept that Rojas and a first Author (Mena and/or Cota) are the real authors of the Comedy and its extension to Tragicomedia, as stated in the acrostic verses.
Keywords: Celestina’s Authorship; Fernando de Rojas; Old Author